2022
DOI: 10.52533/johs.2022.21106
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Virtual Learning on Seizure Control Among Epilepsy Patients in Saudi Arabia

Abstract: Background: The pandemic of COVID-19 has resulted in multiple precautions to control the infection, one of which is transforming students’ schools into virtual classrooms. These new situations may pose additional challenges for some individuals such as epilepsy patients who account for 5.5% of school children (6–18 years). This study aimed to determine the effect of virtual learning on seizure control among epilepsy patients. Methods: This is an online-based cross-sectional study that was performed between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…Only six studies assessed the educational level of the participants; of these, four showed a predominance of high-school educational level [ 24 , 26 , 29 , 31 ]. While the predominance was for bachelor’s degrees of education in two studies [ 27 , 30 ].…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Only six studies assessed the educational level of the participants; of these, four showed a predominance of high-school educational level [ 24 , 26 , 29 , 31 ]. While the predominance was for bachelor’s degrees of education in two studies [ 27 , 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…As for the clinical characteristics of patients with epilepsy included in this systemic review, five studies showed a higher prevalence of generalized tonic-clonic epilepsy type [ 11 , 17 , 23 , 26 , 31 ], five studies showed a predominance of focal epilepsy type [ 21 , 22 , 25 , 27 , 28 ], and three studies did not assess the epilepsy type [ 24 , 29 , 30 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations